Rozwój społeczny człowieka oraz znaczenie relacji interpersonalnych w życiu adolescentów - Głowiak, Daria (Kultura-Społeczeństwo-Edukacja, 2024)
Background: As a social being, humans require contact and interaction with other individuals for proper development at each stage. This dependence is conditioned by multiple factors, such as the necessity to fulfill the mandatory life needs, among which the need to affiliate deserves special attention: that is, the need to belong to a social circle, a community, inside which an individual unit exists and functions every day. One developmental stage where interpersonal relationships receive a deeper meaning is the adolescence period, during which relationships that have existed since childhood undergo a certain kind of transformation. Methods: This is an overview of interpersonal relationships of adolescents, based on available databases. This article aimed to explore the essence of the social functioning of adolescents. Results: The social functioning of teenagers is characterized by an increasing autonomy regarding their parents and caregivers The adolescents on their development path are more and more intensely underlining their place in society as well as their willingness to participate in the social space according to the rules they set, which often leads to intergenerational conflicts. In the life of an adolescent, the most important interpersonal relationships are those established during contact with a peer group. This group, due to its characteristics and developmental potential, serves a range of functions that no other social group can provide to a growing adolescent. Said functions include, among others: the function of organizing free time, the function of egalitarianism of the social group, the function of value distribution, and the function of providing an emotional and psychological background to a young adult. During the growing period, friendly relationships established between two adolescents become increasingly crucial. These relationships frequently pre-intimate features, becoming the potential basis for further romantic relationships formed not only during adolescence but also further down the life of the individual. This article clearly shows the key role of social development in the period of adolescence, as well as in the perspective of the whole human life.